Characterization of Methicillin Resistant Staphylococcus aureus isolated from human and animal samples in Egypt - Bendary, M M; Solyman, S M; Azab, M M; Mahmoud, N F; Hanora, A M (Cellular and Molecular Biology, 2016)
Staphylococcus aureus (S. aureus) has been one of the most problematic pathogens. Methicillin Resistant S. aureus (MRSA) has emerged as a major concern for both human and animal. Antibiotic resistance genes dissemination might be possible between human and animal bacteria. The aim of this study is to show phenotypic and genotypic diversity of human and animal MRSA isolates. Antibiogram typing and biofilm production were used as a primary phenotypic typing tool for the characterization of (40) animal and (38) human MRSA isolates. Genetic typing based on sequencing of 16S rRNA gene and virulence gene profiles were done. Antimicrobial resistance profiles of the animal isolates showed little evidence of widespread of resistance, although this was seen in many human isolates. The biofilm production was detected in higher percentage among animal isolates. Based on the genetic typing and multiple antibiotic resistance (MAR) index, the majority of animal isolates clustered into lineages that were not found in human isolates. Animal and human MRSA isolates showed diversity in antibiotic resistance and virulence gene profiles may be due to host adaptation or chances for contamination between the two hosts were not present in our study.